SOFT SKILLS DEVELOPMENT IN THE ENGLISH LANGUAGE CLASSROOM: STUDENTS’ PERSPECTIVES ON THE PROBLEM - Malykhin, Oleksandr; Aristova, Nataliia; Kugai, Kseniia; Vyshnevska, Maryna; Makhovych, Inna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The present-day globalised world is becoming more dynamic and soft skills become one of the main factors that enable people to participate actively in all aspects of life in it. Moreover, to succeed in personal and professional lives present-day students should be prepared to meet unpredicted challenges that are hard to imagine today. Taking into account the fact that the lists of soft skills are constantly changing and soft skills classifications provided by present-day researchers and practitioners vary greatly, the present research is aimed at finding out students’ perspectives on the importance of soft skills identified by World Economic Forum 2023, on the one hand, and the role of English as a university discipline in soft skills development, on the other hand. To achieve the aim of the study, the researchers developed a questionnaire which included a combination of close-ended and open-ended questions and items on a 5-Likert scale (1 – very unimportant, 2 – unimportant, 3 – neutral, 4 – important, 5 – very important). Data collection lasted for four months and took place in September-December 2023 among students of Kyiv National University of Technologies and Design. To select the research sample, the researchers used a convenience sampling technique. The questionnaires were distributed by hand from researchers to first- and second-year students who studied English as a Second Language. The mixed design of research included qualitative and quantitative processing of the data obtained and the data analysis comprised manual calculations.